2021
DOI: 10.21203/rs.3.rs-244682/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Targeting SARS-CoV-2 receptor-binding domain to cells expressing CD40 improves protection to infection in convalescent macaques

Abstract: Controlling the circulation of the recently emerged SARS-CoV-2 in the human populations requires massive vaccination campaigns. Achieving sufficient worldwide vaccination coverage will require additional approaches to first generation of approved viral vector and mRNA vaccines. Subunit vaccines have excellent safety and efficacy records and may have distinct advantages, in particular when immunizing individuals with vulnerabilities or when considering the vaccination of children and pregnant women.. We have de… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
7
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3
1

Relationship

4
0

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 17 publications
2
7
0
Order By: Relevance
“…In our study (30), an extensive evaluation of the immunological response has been performed with quantification of spike binding antibodies, antibodies inhibiting the attachment of RBD to ACE2, antibodies neutralizing infection, SARS-CoV-2-specific CD4 + and CD8 + T cells producing cytokines and serum cytokine levels (Figure 3, S4, S5, S6). Therefore, based on our mechanistic model we investigated if any of these markers could serve as a mechanistic CoP.…”
Section: αCd40rbd Vaccine On New Cell Infectionmentioning
confidence: 99%
See 1 more Smart Citation
“…In our study (30), an extensive evaluation of the immunological response has been performed with quantification of spike binding antibodies, antibodies inhibiting the attachment of RBD to ACE2, antibodies neutralizing infection, SARS-CoV-2-specific CD4 + and CD8 + T cells producing cytokines and serum cytokine levels (Figure 3, S4, S5, S6). Therefore, based on our mechanistic model we investigated if any of these markers could serve as a mechanistic CoP.…”
Section: αCd40rbd Vaccine On New Cell Infectionmentioning
confidence: 99%
“…We apply our approach to a recently published study (30) testing a protein-based vaccine targeting the receptor-binding domain (RBD) of the SARS-CoV-2 spike protein to CD40 (αCD40.RBD vaccine). Targeting vaccine antigens to Dendritic Cells via the surface receptor CD40 represents an appealing strategy to improve subunit-vaccine efficacy (31)(32)(33)(34) and for boosting natural immunity in SARS-CoV-2 convalescent NHP.…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, the aCD40.RBD vaccine-elicited antibodies cross-neutralized D614G SARS-CoV-2 and the VOCs Alpha (B1.1.7) and, to a lesser extent, Beta (B1.351). This vaccination significantly improved protection against a new high-dose virulent challenge versus that in nonvaccinated convalescent animals (Marlin et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…We have recently reported results on the efficacy of a new generation of subunit vaccines targeting the RBD of the SARS-CoV-2 spike protein to the CD40 receptor (aCD40.RBD) (Marlin et al, 2021). We demonstrated that a single dose of the aCD40.RBD vaccine, injected without adjuvant, is sufficient to boost a rapid increase in neutralizing antibodies in convalescent non-human primates (NHPs) infected six months previously with SARS-CoV-2.…”
Section: Introductionmentioning
confidence: 99%
“…A number of animal models have been developed to study SARS CoV-2 infection including the macaque model, which demonstrated induction of innate, cellular and humoral responses upon infection (Grifoni et al, 2020;Maisonnasse et al, 2020;McMahan et al, 2020;Munster et al, 2020;Rockx et al, 2020) conferring partial protection against reinfection Marlin et al, 2021). Consequently, many early vaccine candidates provided protection in the macaque model including the currently licensed vaccines based on S-specific mRNA delivery (Corbett et al, 2020;Vogel et al, 2021) (BNT162b2, Pfizer/BioNTech;mRNA-1273, Moderna), adenovirus vectors (Mercado et al, 2020;van Doremalen et al, 2020) (ChAdOx1 nCoV-19, Oxford/AstraZeneca; Ad26.COV2.S, Johnson & Johnson) and inactivated SARS-CoV-2 (Gao et al, 2020;Wang et al, 2020b) (PiCoVacc/CoronaVac, Sinovac).…”
Section: Introductionmentioning
confidence: 99%